PENGARUH PROFITABILITAS (ROE), SOLVABILITAS (DER) DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Purnomo, Adi Dwi (Universitas La Tansa Mashiro, 2023)
The value of the company reflects the current state of the company and can describe the company's prospects in the future. The research method uses quantitative methods and uses secondary data types. The sample used is 21 LQ45 companies listed on the IDX for the 2017–2021 period. With a total of 105 data points, selected using a purposive sampling technique. The data analysis used is multiple linear regression analysis with data processing using the SPSS version 26 application. The results showed that the simultaneous test (F test) showed that profitability (ROE), solvency (DER) and firm size had a simultaneous effect on firm value. While the partial test (t test) shows that profitability has no significant effect on firm value, solvency has no significant effect on firm value, and firm size has a significant effect on firm value. With a coefficient of determination or R Square of 0.246 or 24.6%, the firm value can be explained by the variables of profitability, solvency, and firm size. while the remaining 75.4% is influenced by other factors.